PENGARUH PENDEKATAN SAINTIFIK TERHADAP KECEMASAN DAN HASIL BELAJAR PADA MATERI MATRIKS KELAS XI - Dita Aryanti; Ade Mirza; Silvia Sayu (Universitas Tanjungpura, 2021)
AbstractThis research aimed to acknowledge the affect of scientific approach to students' study outcomes and anxiety while studying about matrix in eleventh grade of SMK PGRI Pontianak. The research method used was pre-experimental design, specifically oneshot study. The samples of this research were eleventh grader students in the major of Motor Cycle Technique, chosen by applying purposive sampling technique. Data collected by using study outcomes test and anxiety questionnaire. The data was analyzed by using SPSS 25.0 program for Windows. The analysis of pretest outcomes before scientific approach applied showed that 30% of total students were passed, while the rest were not. After scientific approach applied, the data showed that 85% of total students were passed, the rest were not. Based on the anxiety questionnaire, it showed that 10% felt anxious, 40% felt a bit anxious, 50% not felt any anxiety. Also, there were negative correlation between the students' anxiety and study outcomes, with the correlation score of -0.445.Keywords: Anxiety, Scientific Approach, Study Outcomes,